2012
DOI: 10.1007/s10067-011-1935-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of regulatory T cells in familial Mediterranean fever (FMF)

Abstract: The role of regulatory T cells (T-regs) in familial Mediterranean fever (FMF) was never evaluated. Preliminary studies that we have conducted suggested a rise in the number of regulatory T cells after FMF attacks reaching a maximal level at 7 days. The aim of this study was to evaluate the percentage and activity of regulatory T cells in FMF. Six patients with refractory FMF and six healthy controls were evaluated. The percentage of T-reg cells and forkhead box protein 3 (Foxp3) expression was evaluated and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This was in agreement with Musabak et al, [ 22 ], who stated that CD3, CD4 and CD8 were increased in FMF patients than in the control group indicating that the T cell system is abnormally activated in patients with FMF. Rimar et al, [ 23 ] suggested that regulatory T cells play a role in cutting short FMF acute attacks. This may explain the fact that inflammation in FMF is self - limiting and also the absence of autoantibodies, antigen-specific T cells and tissue damage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was in agreement with Musabak et al, [ 22 ], who stated that CD3, CD4 and CD8 were increased in FMF patients than in the control group indicating that the T cell system is abnormally activated in patients with FMF. Rimar et al, [ 23 ] suggested that regulatory T cells play a role in cutting short FMF acute attacks. This may explain the fact that inflammation in FMF is self - limiting and also the absence of autoantibodies, antigen-specific T cells and tissue damage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Attacks can be triggered by various factors, many of which are still unknown 18,19 . There is an abundance of data about the inflammatory markers in FMF and the clinical effects of chronic inflammation on the clinical presentation 20‐22 . Indeed, proinflammatory cytokines, such as interleukins 6, 8, and 12 and tumor necrosis factor‐α, are elevated in patients with FMF during attacks 20 .…”
mentioning
confidence: 99%
“…18,19 There is an abundance of data about the inflammatory markers in FMF and the clinical effects of chronic inflammation on the clinical presentation. [20][21][22] Indeed, proinflammatory cytokines, such as interleukins 6, 8, and 12 and tumor necrosis factor-a, are elevated in patients with FMF during attacks. 20 However, there are conflicting data in the literature about oxidant/antioxidant status in patients with FMF.…”
mentioning
confidence: 99%
“…Kholoussi and co‐workers detected an increased percentage of CD3 + , CD4 + and CD8 + T cells compared to controls [31]. Rimar et al evaluated the role of regulatory T cells (T regs ) in FMF and proposed that T regs may have a role in terminating FMF attacks [32]. Our results suggest conducting further studies in this context; for example, co‐cultures of T cells and FMF Mo‐DCs to comprehensively examine T cell activation or inhibition.…”
Section: Discussionmentioning
confidence: 99%